Acquired Disorder of Platelet Function Associated with Autoantibodies against Membrane Glycoprotein IIb-IIIa Complex - 1. Glycoprotein Analysis - Meyer, M; Kirchmaier, C M; Schirmer, A; Spangenberg, P; Ströhl, Ch; Breddin, K (Thrombosis and Haemostasis, 1991)
A patient with idiopathic thrombocytopenic purpura developed after splenectomy a thrombasthenia-like severe haemor-rhagic diathesis characterized by a normal or subnormal platelet count, prolonged bleeding time, strongly reduced platelet adhesion to glass and defective platelet aggregation in response to ADP and collagen. In contrast to hereditary thrombasthenia membrane glycoproteins (GP) lib and Ilia were normally present in the patient’s platelets. Immunoelectrophoretic analysis revealed an abnormal behaviour of the patient’s GP IIb-IIIa complex. Autoantibodies against GP IIb-IIIa were detected in Triton-extracted washed platelets. Incubation of normal platelets with plasma from the patient resulted in a similar immunoelectrophoretic abnormality of the GP IIb-IIIa complex indicating that bound autoantibodies (IgG) are responsible for the abnormal immunoelectrophoretic behaviour of the patient’s GP IIb-IIIa complex. Platelet fibrinogen was severely reduced similar to classical thrombasthenia suggesting that the GP IIb-IIIa complex is involved in platelet fibrinogen storage.